Assessing factors influencing return back to work after cholecystectomy: a qualitative research - Keus, Frederik (BioMed Central, 2010)
BACKGROUND: Cholecystectomy causes considerable financial burden on society with a major part caused by sick-leave. There are wide variations in duration of sick-leave. The aim of our study was to identify all aspects that influence the moment of return to work by using focus groups and to compare responses from patients and physicians. METHODS: A qualitative research design was planned using focus group discussions. Four focus group discussions were organized: two patient groups and two physician groups. Employed patients who had recovered after cholecystectomy were included in the patient groups. The physicians groups consisted of general practitioners, surgeons, and company physicians. Three investigators independently searched transcriptions of the sessions for all items relating to return to work. The importance of items and categories were assessed by determining frequencies. RESULTS: In the patients groups physical limitations (35.3%) and individual patient factors (17.5%) were important factors in the duration of sick-leave, while influence or advice comprised only 8.4% of the items. In the physicians groups influence or advice (21.8%) and information-related factors (21.4%) were thought to be important categories. CONCLUSIONS: Physicians perceive their advices as an important factor in patients' duration of sick-leave. In contrast, patients seldom mention this factor and experience physical complaints as the major reason influencing the moment of return to work.